The distribution of freshwater snails of Peninsular Malaysia with notes on the prevalence of schistosoma spindale,the causative agent of cercarial dermatitis. - Ali, Jambari
A survey of freshwater snails of Peninsular Malaysia was conducted from June 1988 until March 1990. Snails were collected primarily from plains and hills of the East and West of the central mountain range. Thirteen species were found in this study,of which Pila scutata,Filopaludina martensi martensi,Melanoides tuberculata,Indoplanorbis exustus,Gryraulus convexiusculus,and Lymnaea auricularia rubiginosa were found to be common and well distributed whereas Pila ampullacea,Filopaludina sumatrensis,Brotia costula ,Brotia spinosa,Bithynia pulchella,Amerianna carinataand Physa sp.were less common and restricted to certain localities. The last two species are thought to be recently introduced to Mlaysia. L.rubiginosa and I.exustus were examined for cercaria of trematodes that may cause cercarial dermatitis. Schistosoma spindale Montgomery,1906 was found from I.exustus and the infection rate of the snails was between 1.7 to 1.7%. The problem was confined only to the central part of the peninsular where paddy is grown by traditional methods and where animals were freed into paddy field outside the planting season.